2005
DOI: 10.1039/b502763m
|View full text |Cite
|
Sign up to set email alerts
|

Selective separation of Am(iii) from lanthanides(iii) by solvent extraction with hydrophobic field of “superweak” anion

Abstract: The weakly coordinating hydrophobic anion TFPB-, whose surface is covered with a hydrophobic field, gives rise to a selective separation of Am(III) from lanthanides(III) in their solvent extraction even with a hard-donor extractant that shows no selectivity for Am(III) in traditional solvent extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…values were found to be in the range of several thousands using Me-BTP even with 0.1 M HNO 3 and as shown from Table 1, such a high S.F. 31 In a previous study, we reported an enhancement in the selectivity (S.F. Carbamoylmethylenephosphine oxide (CMPO), an extensively studied ligand for the actinide partitioning, does not show any selectivity between trivalent actinides and lanthanides.…”
Section: Distribution Studies In [C N Mim]·[ntf 2 ]mentioning
confidence: 76%
“…values were found to be in the range of several thousands using Me-BTP even with 0.1 M HNO 3 and as shown from Table 1, such a high S.F. 31 In a previous study, we reported an enhancement in the selectivity (S.F. Carbamoylmethylenephosphine oxide (CMPO), an extensively studied ligand for the actinide partitioning, does not show any selectivity between trivalent actinides and lanthanides.…”
Section: Distribution Studies In [C N Mim]·[ntf 2 ]mentioning
confidence: 76%
“…For this reason, B 12 F 12 2─ has been called a "weakly coordinating" or "superweak" anion. 25,[27][28][29][30] While a good deal is known about the structures and properties of polyboron chlorides, bromides, and iodides, 18 the literature concerning experimental investigation of polyboron fluoride clusters is relatively sparse. 16,[18][19][20][21][22] For the most part, structural characterization of small boron halide clusters has been achieved by gas-phase electron diffraction or X-ray crystallography of low-temperature B n F m crystals.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Table (1), the extraction efficiency of the metals is higher, due to the occurrence of these concomitant mechanisms. Another effect of the highly hydrophobic anion TFPB has been detailed by Naganawa et al [46]. The non-coordinating anion favors the transfer of dehydrated metallic ion pairs.…”
Section: Effect Of Sacrificial Cationmentioning
confidence: 95%